The Influence of Various Hydration Strategies (Isotonic, Water, and No Hydration) on Hematological Indices, Plasma Volume, and Lactate Concentration in Young Men during Prolonged Cycling in Elevated Ambient Temperatures - Tomasz Pałka; Piotr Michał Koteja; Łukasz Tota; Łukasz Rydzik; Marta Kopańska; Izabela Kaczorowska; Norollah Javdaneh; Wioletta Mikulakova; Hubert Wolski; Tadeusz Ambroży (Biology, 2023)
Background: Increased internal body temperature during dehydration can be accompanied by water–electrolyte imbalances, higher levels of lactate during and after physical exertion, and changes in blood volume. Adequate hydration with carbohydrate–electrolyte fluids during physical activity can prevent dehydration and delay the onset of fatigue, allowing for proper biochemical and hematological reactions during exertion. A suitable drinking plan should consider the pre-exercise hydration level as well as the requirements for fluids, electrolytes, and substrates before, during, and after exercise. The objective of this study was to assess the impact of different hydration strategies (isotonic, water, and no hydration) on hematological indicators (hemoglobin concentration, hematocrit number, erythrocyte count, leukocyte count, and mean corpuscular volume) and lactate concentration during prolonged physical exertion in a high-temperature environment in young men. Methods: The research method was quasi-experimental. The study involved 12 healthy men aged 20.6 ± 0.9 years, who were characterized by a body height (BH) of 177.2 ± 4.8 cm, a body mass (BM) of 74.4 ± 7.6 kg, a lean body mass (LBM) of 61.1 ± 6.1 kg, and a body mass index (BMI) of 23.60 ± 0.48. Measurements were taken of body composition and hematological and biochemical indicators. The main tests consisted of three series of tests separated by a one-week break. During the tests, the men performed a 120 min exercise with an intensity of 110 W on a cycle ergometer in a thermo-climatic chamber at an ambient temperature of 31 ± 2 °C. During exertion, the participants consumed isotonic fluids or water in an amount of 120–150% of the lost water every 15 min. The participants who exercised without hydration did not consume any fluids. Results: Significant differences in serum volume were observed between the use of isotonic beverage and no hydration (p = 0.002) and between the use of isotonic beverage and water (p = 0.046). Immediately after the experimental exercise, hemoglobin values were significantly higher with no hydration than with water (p = 0.002). An even stronger significance of differences in hemoglobin was observed between no hydration and isotonic beverage consumption (p < 0.001). There was a statistically significant difference in the number of leukocytes between the consumption of isotonic beverage and no hydration (p = 0.006). Conclusions: Each active hydration strategy allows for a better maintenance of water–electrolyte homeostasis during physical exertion in a high-temperature environment, and isotonic beverage consumption had a greater impact on hydrating extracellular spaces with the smallest changes in hematological indicators.